Immune responses in mothers of term and preterm very-low-birth-weight infants. - Gennaro, S (1997)
Differences in the levels of immune cell subsets present in peripheral blood have been demonstrated based on sociodemographic factors such as age and race. Postpartal women, who are recovering from the immune changes that are concomitant with pregnancy, have lymphocyte and monocyte values that differ from other populations. A subgroup of postpartal women, mothers who deliver preterm very-low-birth-weight (VLBW) (< or = 1,500 g) infants, may have further differences in values of immune cell subsets and in immune functioning either because of hormonal factors or lifestyle changes or because of the stress they experience after their infant's birth and for the first few months of infant caretaking. This study examined anxiety, depression, and immune cell phenotypes in 30 mothers of VLBW infants and in 30 mothers of healthy term infants over the first 4 postpartal months to determine if mothers of preterm VLBW infants differed from mothers of healthy term infants in psychological and immunologic parameters. Additionally, lymphocyte proliferation and natural killer cell functional assays were performed in a subset of mothers. Mothers of VLBW infants had increased anxiety and decreased lymphocyte proliferation compared to mothers of term infants. When lymphocyte and monocyte subsets were compared over time between the two groups of mothers differences were found in CD8, CD20, CD3-/CD56+, CD14, and HLA class II Ia on monocytes. Mothers with high-fat diets had lower percentages of some monocytes (CD14), lymphocytes (CD4+/CD45RA+), and natural killer cells (CD3-/CD57+) during the first 4 postpartal months.